Maturity levels for private internal investigations: The case of fraud examinations - Gottschalk, Petter (International journal of police science & management, 2017)
The purpose of private internal investigations by fraud examiners is to reconstruct the past by identifying past events and sequences of events. In this article, work by fraud examiners is studied in terms of maturity; introduce a five-stage model for investigation maturity: chaos, mess, disclosure, clarification, and investment. Based on student term papers in a financial crime class, six investigation reports are allocated to levels in the maturity model. The average score for the investigation reports is a level 3 disclosure, where the investigation is problem-oriented and often limited by the mandate. Based on the low average score, this article discusses the privatization of law enforcement, secrecy of investigation reports, lack of disclosure to the police, competence of private investigators, and limits of the investigation mandate.